Democratic Dilemma of Malay Islamic Party: PAS, Coalition Pattern, and Rising Social Issues - Mohd. Izani Mohd. Zain; Mohd. Daud Mat Din (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
This article deliberates on how the Pan-Malaysian Islamic Party (PAS) embraces and weathers the challenges of democracy as a political culture beyond elections. The deliberation analyses the approach and behaviors of the party within a period of three general elections (GE), namely the GE12 in 2008, GE13 in 2013, and GE14 in 2018. Through qualitative approach and in-depth interviews with key PAS leaders, this article discusses PAS participation with the Pakatan Rakyat (PR), Muafakat Nasional (MN), and Perikatan Nasional (PN), which demonstrated the PAS’s unchartered undertaking to accept democracy as a political culture and not as a tool to achieve political power through an election. While it is trite to take the position that elections are the truest form of democracy, they can foster greater inclusivity, which can take place in both political and non-political realms.